ECOTOURISM DEVELOPMENT OF KERUJUK VILLAGE, NORTH LOMBOK - Rosianna Sianipaar; Juliana Juliana; Rudy Pramono; Diena M.Lemy; Amelda Pramezwary (Jurnal Ekonomi, 2023)
Kerujuk Ecotourism is located in West Pemanang Village, Pemanang District, North Lombok Regency. This ecotourism was formed when the tragedy of a landslide and flood occurred in 2002. The purpose of this research is first to analyze the ecotourism potential of North Lombok Kerujuk Ecotourism. Based on the research background, the formulation of the problem used in discussing this research is as follows: 1. What is the condition of ecotourism in Kerujuk North Lombok. 2. How is the development of ecotourism in KerujukNorth Lombok. This research aims to examine the development of ecotourism in Kerujuk, North Lombok. The method used in this research is qualitative research method. The Kerujuk Ecotourism Development has the potential to be developed with the collaboration of all stakeholders. The direction of developing Kerujuk Ecotourism can be developed with community-based tourism because it already has a tourism awareness group that will initiate the development of this ecotourism. This ecotourism needs to implement ecotourism principles and the concept of community-based tourism to be more organized and benefit the community. This research must continue due to data limitations and field observation time.